Implementation of Agenda Setting Theory on the Role of Islamic Higher Education Public Relations in Building Moderate Islamic Discourse in Digital Media - Dimas Prasetya; Ryan Marina; Arditya Prayogi; Lia Afiana (Lembaga Pengembangan Kinerja Dosen, 2024)
The spread of religion-based radicalism in digital spaces requires strategic communication efforts from Islamic higher education institutions to build counter-narratives through the strengthening of moderate Islamic discourse. This study aims to analyze the implementation of Agenda Setting Theory in the role of Public Relations at Islamic Religious Higher Education Institutions in developing moderate Islamic discourse through digital media. Using a qualitative approach with a case study design, data were collected through in-depth interviews and documentation analysis of both institutions’ communication activities. The findings reveal that PR plays four major roles in disseminating moderate Islamic values: as a communication technician, communication facilitator, expert prescriber, and problem-solving facilitator. Through the application of the Agenda Setting Theory, PR successfully establishes key issues such as religious moderation and humanism as the main focus of the universities’ digital communication. Strategies employed include maintaining visual identity consistency, strengthening media networks, and aligning messages with institutional visions and missions. This study concludes that PR at PTKI functions not only as an information manager but also as a social change agent and a driver of digital da’wah that supports moderate Islamic discourse in digital media.